LIBERAL MIND IN A CONSERVATIVE PARTY : intellectuals and the liberal party of australia. - ROBINSON, GEOFFREY (ROUTLEDGE, 2025)
Robinson analyses the peculiarly Australian intellectual tradition of liberal conservatism within the mainstream centre-right Liberal Party of Australia. Conservative intellectuals in Australia have forged a pragmatic, sceptical and utilitarian liberal conservatism focused on the tasks of government. It remains distant both from the romantic and organicist ideas of the populist right and the simplicities of libertarianism.Focusing on key figures within this tradition, Robinson tracks the progress of Australian liberal conservatism over the years through its origins in the work of David Hume to the thoughts of Peter Coleman, David Kemp and Andrew Norton before moving forward to George Brandis and Gregory Melleuish. The Liberal Party of Australia has appealed successfully to the conservative sentiments of voters in a liberal society. The Liberal Mind in a Conservative Party tells the story of seven intellectuals who helped make this possible. Peter Coleman drew on John Anderson, Georges Sorel and Michael Oakeshott to champion neoconservatism. He argues that this potent political ideology has shaped a distinct political identity, which rejects conservative traditionalism, and libertarian economics, while defending a pragmatic approach to capitalism.A fascinating read for students and scholars of Australian politics, this book will also be of great value to readers with an interest in international centre-right politics.